Physical Activity and The Strength of Bone in Menopause Patients in National Sports Hospital in 2017 - Laras Bani Waseso; Basuki Supartono; Cut Fauziah (Berkala Kedokteran, 2018)
Abstract: Osteoporosis is three times more likely to happen to menopause patients with low physical activity because it causes the bone mass to decrease. Standard examination for osteoporosis is a bone mass examination or also known as BMD (Bone Mass Densitometry). This research aims to identify the correlation between physical activity and bone strength in menopause patients. This is an observational analytical research which used cross-sectional design. The sample consists of 74 patients from Kemenpora National Hospital in 2017. The data were analyzed by using Chi-square test. The result shows that 37% of low physical activity patients have normal bone strength, 63% of which have osteopenia and 20% of the patients have osteoporosis. Meanwhile, 52% of medium physical activity patients have normal bone strength, 19% of the patients have osteopenia, and 33% of the patients have osteoporosis. 16% of patients with high physical activity have normal bone strength, 18% of the patients have osteopenia, and 47% of the patients have osteoporosis. This research proves that there is a correlation between physical activity and bone strength in menopause patients (p = 0,004). Keywords: Physical Activity, Bone Mass Densitometry, Menopausal Women